2012
DOI: 10.1097/mnh.0b013e32835021bd
|View full text |Cite
|
Sign up to set email alerts
|

New insights into hypertension-associated erectile dysfunction

Abstract: Purpose of review Erectile dysfunction (ED) is recognized as a quality of life disorder that needs to be treated. Currently, it is estimated to affect as many as 30 million American men. Thirty percent of hypertensive patients complain of ED. The understanding of common mechanisms involved in the etiology of ED associated with hypertension, and the investigation of antihypertensive drugs that impact ED, will provide important tools toward indentifying new therapeutic targets that will improve the quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 49 publications
8
84
1
1
Order By: Relevance
“…Those factors, which regulate contraction and relaxation of vascular smooth muscle, determine the state of the penis (flaccidity versus erection) (Andersson, 2001;Tostes et al, 2007;Nunes et al, 2012). The flaccid state is mainly mediated by the release of norepinephrine from adrenergic nerve terminals and other vasoconstrictors, such as endothelin-1 and angiotensin II (Sáenz de Tejada et al, 1989, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Those factors, which regulate contraction and relaxation of vascular smooth muscle, determine the state of the penis (flaccidity versus erection) (Andersson, 2001;Tostes et al, 2007;Nunes et al, 2012). The flaccid state is mainly mediated by the release of norepinephrine from adrenergic nerve terminals and other vasoconstrictors, such as endothelin-1 and angiotensin II (Sáenz de Tejada et al, 1989, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicate that drugs used in the treatment of hypertension can indeed deteriorate sexual function, but such an effect appears mainly with older generation drugs (older beta blockers, diuretics), while newer agents (nebivolol, renin-angiotensin-aldosterone system blockers) might even improve sexual function [ 27 ]. On the other hand, hypertension appears to cause ED per se, through a multitude of mechanisms that include prolonged exposure to elevated levels of systemic blood pressure, endothelial dysfunction and circulation of vasoactive substances (with a pivotal role of angiotensin II) that lead to structural and functional alterations in the penile arteries [ 28 ]. Penile doppler studies have shown that the presence of hypertension is associated with a approximately twofold increase in the likelihood of having an abnormal penile blood fl ow [ 29 ].…”
Section: Is Erectile Dysfunction a Target Organ Damage Per Se?mentioning
confidence: 98%
“…Erectile dysfunction can occur due to both physiological and psychological reasons including diabetes, kidney disease, chronic alcoholism, multiple sclerosis, atherosclerosis, vascular disease, and neurologic disease [69][70][71][72]. cGMP specific phosphodiesterase inhibitors such as Viagra® have been used to treat erectile dysfunction by suppressing cGMP and extending erection time.…”
Section: Optogenetic Network For the Treatment Of Penile Erectionmentioning
confidence: 99%